Legalization of Arak Bali in Online News Headlines: Critical Discourse Analysis - Nadya Inda Syartanti (Humaniora, 2021)
In 2020, arak bali, traditional liquor from Bali, was legalized by the Governor of Bali, I Wayan Koster. This research aimed to reveal the construction of news headlines about the legalization of arak Bali. Data were sourced from various online news media (detiknews.com, kompas.com, tribunnews.com), collected by selecting news headlines with the keywords arak Bali and pelegalan, and analyzed using Norman Fairclough’s critical discourse analysis. The results showed that the six news headlines used linguistic tools such as selected vocabulary that focused on the word legal, grammatical units that were dominated by clauses, syntactic functions dominated by the discourse’s topicalization, and a form of news emphasizing the statement of the legalization of arak bali by Koster. The mindset of the Balinese towards arak bali cannot be separated from their predominant belief system, Hinduism. Meanwhile, Koster’s commitment to arak bali shows his ideology, as an indigenous Balinese individual, of preserving Balinese culture and traditions. Finally, the headlines on the legalization of arak bali occurred at the situational level, with Balinese people welcoming the legalization of arak bali, resulting in Koster planning to hold an arak bali festival as a means of promoting and preserving Balinese culture.